1972
DOI: 10.1126/science.178.4067.1300
|View full text |Cite
|
Sign up to set email alerts
|

Australia Antigen (Hepatitis B Antigen): A Conformational Antigen Dependent on Disulfide Bonds

Abstract: Reduction and alkylation of purified hepatitis-associated Australia antigen (hepatitis B antigen) resulted in a total loss of serologic activity. The reduced and alkylated protein formed a single band with a sedimentation coefficient of 31S on analytical ultracentrifugation, and no subunits were detected by Sephadex gel filtration. Although this preparation induced a delayed hypersensitivity response when injected into guinea pigs, it failed to stimulate humoral antibody formation. The data suggest that hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

1980
1980
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 14 publications
2
41
0
2
Order By: Relevance
“…Prior to evaluation of mutant HDV particles for infectivity, the particles were examined for antigenicity as an attempt to identify changes induced by the cysteine mutations in the "a" determinant. It was previously shown that reactivity of HBV particles with anti-HBsAg antibodies was dependent upon envelope protein disulfide bonds (39) and that antigenicity of SVPs carrying AGL cysteine mutations was drastically affected (27). Here, we measured the reactivity of each cysteine mutant in two commercial immunoassays (Monolisa HBsAg Ultra from Bio-Rad and ETI-MAK-4 HBsAg from Dia-Sorin).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to evaluation of mutant HDV particles for infectivity, the particles were examined for antigenicity as an attempt to identify changes induced by the cysteine mutations in the "a" determinant. It was previously shown that reactivity of HBV particles with anti-HBsAg antibodies was dependent upon envelope protein disulfide bonds (39) and that antigenicity of SVPs carrying AGL cysteine mutations was drastically affected (27). Here, we measured the reactivity of each cysteine mutant in two commercial immunoassays (Monolisa HBsAg Ultra from Bio-Rad and ETI-MAK-4 HBsAg from Dia-Sorin).…”
Section: Resultsmentioning
confidence: 99%
“…The latter would not be surprising, since conformational effects in HBsAg have long been known. For example, although the molecule contains numerous potential trypsin cleavage sites, only one of these (Lys-122) is susceptible to tryptic attack, even under dissociating conditions (24); similarly, antibodies raised to native HBsAg particles recognize denatured p24s polypeptides poorly or not at all (35).…”
Section: Discussionmentioning
confidence: 99%
“…The antigenicity and immunogenicity of this protein (designated S-protein) depends on the maintenance of disulphide bonds (Vyas et al, 1972;Sukeno et al, 1972;Dreesman et al, 1973). The open reading frame on HBV DNA coding for S protein (Charnay et al, 1979;Peterson et al, 1977) has the capacity to code for a protein consisting of 389 to 400 amino acids (depending on the antigenic subtype of HBV).…”
Section: Introductionmentioning
confidence: 99%